2016
DOI: 10.1016/j.livsci.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dietary forage and crude protein levels on the shedding of Escherichia coli O157:H7 and Listeria in dairy cattle feces

Abstract: A B S T R A C TThe shedding of Escherichia coli O157:H7 and Listeria monocytogenes in the feces of ruminants and the consequential risk to the public and environmental health is well reported. However, the influence of dietary manipulation on the shedding of fecal bacteria is not well understood. This study was conducted to improve understanding of the relationship between dietary feed composition and shedding of E. coli O157:H7 and Listeria spp. in dairy feces. Twelve cows were randomly assigned to four treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Differences in E. coli concentration in fresh faeces excreted by livestock, wildlife, and wildfowl are not unexpected, and studies have reported variability in E. coli shedding across different sources [ 30 ]. Differences in the initial concentration of E. coli likely reflect the diet associated with deer, dairy cows, and geese, and they also reflect the digestive tract characteristics and likely the cross-contamination from exposure to other animals in their habitats [ 31 , 32 ]. The dairy cow and deer faeces used in our study were collected from a working dairy farm and a deer park, respectively, where the animals were exposed to formulated feeds in addition to pasture.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in E. coli concentration in fresh faeces excreted by livestock, wildlife, and wildfowl are not unexpected, and studies have reported variability in E. coli shedding across different sources [ 30 ]. Differences in the initial concentration of E. coli likely reflect the diet associated with deer, dairy cows, and geese, and they also reflect the digestive tract characteristics and likely the cross-contamination from exposure to other animals in their habitats [ 31 , 32 ]. The dairy cow and deer faeces used in our study were collected from a working dairy farm and a deer park, respectively, where the animals were exposed to formulated feeds in addition to pasture.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli O157:H7 and Listeria spp. levels were determined using selective and differential agar media, as described by Biswas et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Additional knowledge gaps include the survival of pathogens in animal manure in ICLS systems and subsequent infection or transmission to other individuals within the herd or potential implications for food safety. A recent study showed that pathogens in manure can survive for considerable amount of time under open-air conditions (Biswas et al, 2016).…”
Section: What Don't We Know?mentioning
confidence: 99%